Digital gamification in EFL vocabulary learning: The Effect of Wordwall platform on students’ vocabulary mastery - Andika Andika; Ayu Sukma Wardani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2026)
This study investigates the effectiveness of the Wordwall platform as a digital learning tool in improving students’ English vocabulary mastery and examines students’ responses toward its implementation. The study was conducted in response to the need for more interactive and engaging instructional media in vocabulary learning. A quantitative approach employing a one-group pretest–posttest design was used. The participants were seventh-grade students, and the data were collected through vocabulary tests and a questionnaire. The pretest and posttest scores were analyzed using descriptive statistics and a paired-sample t-test, while students’ responses were analyzed using percentages and mean scores. The results revealed a significant improvement in students’ vocabulary mastery after the implementation of the Wordwall platform. In addition, the questionnaire findings indicated that students had positive perceptions of the Wordwall platform, viewing it as engaging, easy to use, and helpful for learning vocabulary. However, some challenges related to internet access were also identified. These findings suggest that the Wordwall platform can be an effective tool for enhancing vocabulary learning in EFL classrooms.